2022
DOI: 10.3389/fmed.2022.849990
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 Producing Lymphocytes Cause Dry Eye and Corneal Disease With Aging in RXRα Mutant Mouse

Abstract: PurposeTo investigate IL-17 related mechanisms for developing dry eye disease in the Pinkie mouse strain with a loss of function RXRα mutation.MethodsMeasures of dry eye disease were assessed in the cornea and conjunctiva. Expression profiling was performed by single-cell RNA sequencing (scRNA-seq) to compare gene expression in conjunctival immune cells. Conjunctival immune cells were immunophenotyped by flow cytometry and confocal microscopy. The activity of RXRα ligand 9-cis retinoic acid (RA) was evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 56 publications
0
17
1
Order By: Relevance
“…Removal of the major extraorbital lacrimal gland induces severe aqueous deficient dry eye and is the basis for a well-characterized animal model 18 20 . We analyzed retention of an antibody to IL-17A because intraperitoneal injection of antibodies to IL-17A has been shown to reduce dry eye signs in mouse models 21 23 . The antibody was labeled with Alexa Fluor 488, and the presence on the ocular surface was followed by fluorescence photography.…”
Section: Resultsmentioning
confidence: 99%
“…Removal of the major extraorbital lacrimal gland induces severe aqueous deficient dry eye and is the basis for a well-characterized animal model 18 20 . We analyzed retention of an antibody to IL-17A because intraperitoneal injection of antibodies to IL-17A has been shown to reduce dry eye signs in mouse models 21 23 . The antibody was labeled with Alexa Fluor 488, and the presence on the ocular surface was followed by fluorescence photography.…”
Section: Resultsmentioning
confidence: 99%
“…Further, Chauhan et al were able to show that DED inflammation was lower in mice treated with anti-IL–17A antibodies. 7 , 56 Almost at the same time, Alam et al 39 found that the Pinkie mouse strain with a loss-of-function RXRα mutation has increased signs of DED and a 4-fold greater percentage of conjunctival γδ T cells with a higher expression of IL-17 under homeostatic conditions. Notably, disruption of the IL-17A signal has been associated with the development and progression of various autoimmune or autoinflammatory diseases, such as rheumatic diseases.…”
Section: Discussionmentioning
confidence: 96%
“… 31 , 33 , 35 37 Interestingly, γδ T cells are abundantly distributed in the conjunctiva and highly express IL-17A in response to conjunctival commensals, and of these approximately one-half are Vγ4 + subset. 23 Meanwhile, mice with a loss-of-function RXRα mutation exhibited a 4-fold greater percentage of conjunctival γδ T cells with increased expression of IL-17, 39 and the development and progression of DED seem to be highly dependent on IL-17A. 9 , 13 , 38 However, the contribution of γδ T cells itself in the conjunctiva to the occurrence of DED is not known.…”
mentioning
confidence: 99%
“…Using the RXRα Pinkie mouse model, which develops many characteristics of DED including goblet cell loss, it was recently reported that IL-17+ γδ T cells found in the conjunctiva contribute to MMP-9 production and goblet cell loss, both of which could be blocked with an anti-IL-17 monoclonal antibody. 74 IL-17 is an important contributor to SS pathogenesis. 75 77 Additionally, activation of P2X7R, which is elevated in the lacrimal glands of NOD.H-2 h4 DKO mice ( Fig.…”
Section: Discussionmentioning
confidence: 99%